2006
DOI: 10.1631/jzus.2006.b0342
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between mycoplasma lipid-associated membrane proteins and the host cells

Abstract: Abstract:Mycoplamas are a group of wall-less prokaryotes widely distributed in nature, some of which are pathogenic for humans and animals. There are many lipoproteins anchored on the outer face of the plasma membrane, called lipid-associated membrane proteins (LAMPs). LAMPs are highly antigenic and could undergo phase and size variation, and are recognized by the innate immune system through Toll-like receptors (TLR) 2 and 6. LAMPs can modulate the immune system, and could induce immune cells apoptosis or dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
0
23
0
4
Order By: Relevance
“…Mycoplasmas are bacteria with the smallest genome (580-2200 kb), with a relatively high A þ T content (67-76%) [1]. With this basic genome, the bacteria have to obtain most nutrients from the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasmas are bacteria with the smallest genome (580-2200 kb), with a relatively high A þ T content (67-76%) [1]. With this basic genome, the bacteria have to obtain most nutrients from the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Despite of its simple structure and function, the way that ureaplasmas interact with their host is not totally elucidated, although studies demonstrated that the way of parasitism in the host cell is primarily extra-cellular (You et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The Mycoplasma is bound by a single limiting cytoplasmic membrane with abundant lipoproteins known as lipid-associated membrane proteins (LAMPs) (You et al, 2006). Most of the LAMPs are exposed to the extracellular milieu and some have either been described as virulence factors (Szczepanek et al, 2010) or targets for antibodies (Washburn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%